Comparison of Antiaging and Antioxidant Activities of Protocatechuic and Ferulic Acids - Ermi Girsang; I Nyoman Ehrich Lister; Chrismis Novalinda Ginting; Maulidwina Bethasari; Annisa Amalia; Wahyu Widowati (Molecular and Cellular Biomedical Sciences, 2020)
Background: Skin-aging is a progressive changes in the skin combine with cumulative extrinsic factors which are mostly caused by free radicals caused by exposure to lots of free radicals molecules from pollutant, wrongly food intake, or too much sun bathing. These free radicals can be tackled by a treatment using antioxidants. Prevention of aging can be done by escalating antioxidant intake. Protocatechuic acid (PCA) and Ferulic acid (FA) have been known for their scavenging properties on free radicals and antiaging activity. Antioxidant and antiaging activity of both compounds have not been compared comprehensively before. Hence, current study was conducted to compare the potential of PCA and FA for their antioxidant and antiaging activities using various methods.Materials and Methods: Antioxidant analysis of PCA and FA was conducted using H2O2 scavenging assay, 2,2’-azinobis-3-ethylbenzo-thiazoline-6-sulfonic acid (ABTS), 2,2-diphenyl-1-picrylhydrazil (DPPH), and ferric reducing antioxidant power (FRAP). Meanwhile, antiaging activities of PCA and FA were examined using inhibitory activities of tyrosinase, collagenase, elastase, hyaluronidase and tyrosinase.Results: IC50 of scavenging activity of ABTS were 125.18 µg/mL (PCA) and 35.55 µg/mL (FA), inhibition activity of collagenase were 126.16 µg/mL (PCA) and 52.85 µg/mL (FA) and inhibition activity of tyrosinase were 246.42 µg/mL (PCA), 253.58 µg/mL (FA).Conclusion: In conclusion, FA has better ABTS scavenging and collagenase inhibition activities compared to PCA. Meanwhile, PCA has better activity of tyrosinase inhibition than FA.Keywords: antioxidant, antiaging, ferulic acid, protocatechuic acid